Morphological and Histological Study of the Pancreas of quail (Coturnixcoturnix) - Dhaferah Jaafar A. Al Fatlawi (Journal of Global Pharma Technology, 2018)
Study was carried out on  seven pairs of adult quail ((Coturnixcoturnix), The pancreas was excised from the duodenum rapidly after slaughter of the birds, the observations showed that there's no difference of structure features between sex (male and female of quail pancreas. The Pancreas is situated on the right side of abdominal cavity in the area between the ascending and descending duodenal loops, attached with the alimentary tract covered with capsules, the parenchyma of pancreas divided it to lobules by fascicles of connective tissue extended from capsule. The parenchyma of pancreas divided in to two kinds of glands exocrine and endocrine gland, the exocrine composed of serous acini cells and ductal cells, the duct system composed of intercalated duct attached to the centroacinar cells inside the lumen of serous acini, followed by intralobular duct, interlobular duct, and main duct (pancreatic duct) Endocrine gland divided in to two types of islets, the large one Alpha islets, and the small types Beta islets, supplied by rich network of blood vessels. Each ofducts, aggregation of lymphatic tissue and blood vessels can be seen in section of parenchyma. No clear boundaries between the exocrine portion and Islets of Langer hans. In conclusion the Anatomical features and histological structure of quail (Coturnixcoturnix) pancreas was found to be similar to that of other avian speciesKey words: Morphological. Histological. Pancreas, Adult. Quail. Coturnixcoturnix.